Leitura da legislação brasileira na internet: estratégias eficientes de navegação e compreensão - Giovana de Sousa Rodrigues (2018)
The object of this research is the navigation and comprehension strategies adopted in reading the law, on the Internet, by readers with different levels of proficiency in juridical texts. The approach adopted is qualitative, exploratory and observational. Objectives - The general objective was to carry out a survey of these strategies, with a view to (i) proposing guidelines for teaching and learning juridical literacy in basic education and other processes of citizenship promotion and (ii) proposing changes, on government sites, to improve the quality and accessibility of juridical information. Methodology Data collection included the resolution of juridical questions, through consultation on the Internet, by law specialists, law students and high school students, using the think-aloud technique. Results In order to solve the juridical questions, the informants read not only laws and other normative acts, but also texts from the various sources in which juridical information is made. This process required them to use specific strategies for locating, evaluating and integrating information made available on the internet. These strategies were not efficient or inefficient on their own; the efficiency of the process depended on the ways in which the various strategies were monitored and conjugated. To this end, the previous experiences of reading and navigating of the informants, their academic background and their professional experience in the field of Law, their cognitive abilities, their familiarity with the legal matter dealt with in the questions and their previous experiences of citizen participation have contributed. Thus, in spite of the fact that, in the set of the tasks performed, the specialists performed better than the law students, and these students performed better than the high school students (according to the assumption), informants of the three groups, in some situations, presented a performance above or below the assumption. This performance was also influenced by the quantity and quality of the information made available on the Internet and by the navigation resources of the sites consulted, which evidenced the need to improve the elaboration and the means of making available juridical information, especially in the public administration. As a conclusion It was found that juridical literacy at elementary levels is possible and necessary, and should take place in a gradual, continuous, critical and meaningful way. The necessary increase in the quality of juridical information and resources for its availability in the public administration, as well as the teaching and learning of juridical literacy, due to its complexity, require the collaborative effort of the various spheres of public administration, of the three Powers. For this, the researches at the intersection of the fields of Linguistics and Law have much to contribute and a vastness to go through.